Upaya Meningkatkan Hasil Belajar IPA Materi Bioteknologi Melalui Penerapan Model Pembelajaran Kooperatif Tipe STAD Peserta Didik Kelas IX.1 UPTD SMPN 1 Kecamatan Guguak Tahun Pelajaran 2020/2021 - Yenfitriza Yenfitriza (Pendidikan Biologi FKIP UMMY, 2021)
This research is motivated by the low learning outcomes of students in science class IX.1 UPTD SMPN 1 Guguak District. The purpose of this study was to determine the improvement of Science Learning Outcomes for Biotechnology Materials through the Application of the STAD Type Cooperative Learning Model for Class IX.1 UPTD SMPN 1 Guguak Subdistrict for the 2020/2021 Academic Year. This type of research is Classroom Action Research (CAR) which consists of two cycles, and each cycle consists of two meetings. The subjects of this study were students of class IX.1 UPTD SMPN 1 Kec. Guguak totals 30 students. The results of the research in the first cycle were 22 students who had reached the KKM, or 73.3% of students had been declared complete. This means that the indicators of research success have not yet been achieved. So the research continued to the next cycle. In cycle II, 27 students had reached the KKM, or 90% of the students had completed. This means that it has reached the established indicators of research success. So that the research is said to be successful and is not continued to the next cycle. So it can be concluded that there is an increase in Science Learning Outcomes for Biotechnology Materials through the Application of the STAD Type Cooperative Learning Model for Class IX.1 UPTD SMPN 1 Guguak District for the 2020/2021 Academic Year